Role of N-Acetylcysteine and Coenzyme Q10 in the Amelioration of Myocardial Energy Expenditure and Oxidative Stress, Induced by Carbon Tetrachloride Intoxication in Rats - Nayira A. Abd Elbaky; Naglaa F. El-Orabi; Laila M. Fadda; Omar H. Abd-Elkader; Hanaa M. Ali (SAGE Publishing, 2018)
This study is designed to evaluate the potential impact of N-acetyl cysteine (NAC) and coenzyme Q10 (CoQ10) each alone or in combination against carbon tetrachloride (CCl 4 )-induced cardiac damage in rats. Animals were treated with CCl 4 in single intraperitoneal dose of 1 mL/Kg body weight; CCl 4 -intoxicated animals were pretreated with 20 mg/kg/d NAC or pretreated with 200 mg/kg/d CoQ10 or NAC and CoQ10 with the same previously mentioned doses. Carbon tetrachloride-intoxicated rats showed a significant elevation in nitric oxide and lipid peroxides and downregulation in reduced glutathione level and calcium adenosine triphosphatase. Cardiac glycolytic enzymes levels such as lactate dehydrogenase, phosphofructokinase, and hexokinase were declined coupled with a reduction in glucose content after CCl 4 treatment. Moreover, myocardial hydroxyproline level was significantly increased after CCl 4 -treatment indicating accumulation of interstitial collagen. N-acetyl cysteine and/or CoQ10 effectively alleviated the disturbances in myocardial oxidative stress and antioxidant markers. These antioxidants effectively upregulated the reduction in cardiac energetic biomarkers due to CCl 4 treatment. N-acetyl cysteine and/or CoQ10 significantly decreased hydroxyproline level compared to that of CCl 4 -treated rats. The current data showed that the aforementioned antioxidants have a remarkable cardioprotective effect, suggesting that they may be useful as prophylactic agents against the detrimental effects of cardiotoxins.